Operational amplifiers theory and design - Huijsing, Johan H. 1938-; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Operational Amplifiers Theory and Design, Second Edition presents a systematic circuit design of operational amplifiers. Containing state-of-the-art material as well as the essentials, the book is written to appeal to both the circuit designer and the system designer. It is shown that the topology of all operational amplifiers can be divided into nine main overall configurations. These configurations range from one gain stage up to four or more stages. Many famous designs are evaluated in depth. Additional chapters included are on systematic design of µV-offset operational amplifiers and precision instrumentation amplifiers by applying chopping, auto-zeroing, and dynamic element-matching techniques. Also, techniques for frequency compensation of amplifiers with high capacitive loads have been added. Operational Amplifiers Theory and Design, Second Edition presents high-frequency compensation techniques to HF-stabilize all nine configurations. Special emphasis is placed on low-power low-voltage architectures with rail-to-rail input and output ranges. In addition to presenting characterization of operational amplifiers by macro models and error matrices, together with measurement techniques for their parameters it also develops the design of fully differential operational amplifiers and operational floating amplifiers. Operational Amplifiers Theory and Design, Second Edition is carefully structured and enriched by numerous figures, problems and simulation exercises and is ideal for the purpose of self-study and self-evaluation.
Summary -- Introduction. Notation. 1. Definition of Operational Amplifiers -- 2. Macromodels -- 3. Applications -- 4. Input Stages -- 5. Output Stages -- 6. Overall Design -- 7. Design Examples -- 8. Fully Differential Operational Amplifiers -- 9. Operational Floating Amplifiers (Ofa) -- 10. Low Noise and Low Offset Amplifiers -- Biography -- Index.
Electronic reproduction.
Keywords: Operational amplifiers; Electronic books